Prospect evaluation of shallow I-35 reservoir of NE Malay Basin offshore, Terengganu, Malaysia - Osama Akhtar Janjua, Ali Wahid, Ahmed Mohamed Ahmed Salim, M Nas, . (2016)
A potential accumulation of hydrocarbon that describes significant and conceivable drilling target is related to prospect. Possibility of success estimation, assuming discovery of hydrocarbons and the potential recoverable quantities range under a commercial development program are the basis of Prospect evaluation activities. The objective was to find the new shallow prospects in reservoir sandstone of I–Formation in Malay basin.